Reframing Islamic Epistemology: Reconciling Traditional Ilm al-Usūl with Contemporary Epistemic Challenges in Muslim Societies - Rahmad Setyawan; Asmuki Asmuki; Holil Holil; Djuwairiyah Djuwairiyah (International Forum of Researchers and Lecturers, 2024)
This article examines the possibility of reconstructing Islamic epistemology through the integration of classical Ilm al-Usūl principles with modern epistemic challenges. The revivalist/textualist, reformist/maqāṣidī, and critical-hermeneutic approaches to Islamic epistemology are discussed, each contributing a unique perspective on the reconciliation of traditional Islamic knowledge with modern intellectual developments. The main objective is to analyze how Ilm al-Usūl can maintain its normative foundations while responding to contemporary issues such as misinformation, the growing complexity of scientific knowledge, and the fragmentation of epistemic authority. By examining maqāṣid al-sharīʿa, ḥujjiyyah, and other core concepts within Ilm al-Usūl, the article proposes a conceptual bridge that balances revelation with empirical data, fostering a more adaptive epistemological framework. The research design follows a conceptual-analytical library approach, utilizing both classical Islamic legal texts and modern epistemological literature, including social epistemology and theories of knowledge justification. The results reveal that the reconstruction model offers a more comprehensive solution compared to traditional approaches, addressing modern epistemic challenges without abandoning foundational Islamic principles. The discussion highlights the importance of modernizing the methodology to include empirical tools like data literacy and ethical considerations, while maintaining the normative integrity of Islamic knowledge. The article concludes by presenting practical implications for Islamic education and religious authority, recommending the integration of scientific literacy and modern epistemic practices into Ilm al-Usūl curricula. It also suggests future research on specific case studies and the development of modern indicators of epistemic authority.